2021
DOI: 10.1136/bmjgh-2021-006982
|View full text |Cite
|
Sign up to set email alerts
|

Where there is no local author: a network bibliometric analysis of authorship parasitism among research conducted in sub-Saharan Africa

Abstract: IntroductionAuthorship parasitism (ie, no authors affiliated with the country in which the study took place) occurs frequently in research conducted in low-income and middle-income countries, despite published recommendations defining authorship criteria. The objective was to compare characteristics of articles exhibiting authorship parasitism in sub-Saharan Africa to articles with author representation from sub-Saharan African countries.MethodsA bibliometric review of articles indexed in PubMed published from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 35 publications
4
37
0
Order By: Relevance
“…For example, a recent bibliometric analysis published in October 2021 analyzed the concept of authorship parasitism, when none of the study authors were affiliated with the LMIC in which a study took place. 19 This paper observed that 14.8% of 32,061 published studies in SSA indexed in PubMed between 2014 and 2018 fell into this category. SSA authorship under-representation has also been described in SSA studies in other specific fields such as infectious disease, 8 geoscience, 20 COVID-19 pandemic research, 9 and collaborative research.…”
Section: Discussionmentioning
confidence: 91%
“…For example, a recent bibliometric analysis published in October 2021 analyzed the concept of authorship parasitism, when none of the study authors were affiliated with the LMIC in which a study took place. 19 This paper observed that 14.8% of 32,061 published studies in SSA indexed in PubMed between 2014 and 2018 fell into this category. SSA authorship under-representation has also been described in SSA studies in other specific fields such as infectious disease, 8 geoscience, 20 COVID-19 pandemic research, 9 and collaborative research.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, prior research on authorship 'parasitism' in research conducted in sub-Saharan Africa has found that studies without any local authorship were less likely among articles with >10 authors. 3 Together, these findings may be explained by larger authorship groups being more likely to include LMIC authors in token middle authorship positions to ensure formal or informal expectations for local author inclusion are met. Additionally, certain subfields within GEM, such as disaster and humanitarian response appear to have even greater inequities; further research is needed to understand how research within crisis settings may differ from general GEM research, and how long-standing colonial structures in the humanitarian sector may influence authorship decisions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite the field's emphasis on equity, a growing body of literature has highlighted pervasive inequities in global health research that mirror existing power asymmetries between researchers based in low and middle-income countries (LMICs) versus high-income countries (HICs). [2][3][4][5][6] One such inequity is seen in authorship representation in global health research conducted in LMICs. 2 4 7 Previous evaluations of authorship equity within the general global health literature have shown under-representation of LMIC authors and a predominance of authors affiliated with HIC institutions.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…African researchers who contribute to data collection in such projects are not always credited for their work. A 2021 study 17 revealed that about 15% of 32,061 articles on global health research conducted in sub-Saharan Africa had no authors based in the country in which the research took place.…”
mentioning
confidence: 99%